Anti-money laundering practices in banks: customer's awareness and acceptance in India. Issue 3 (4th July 2016) - Viritha, B.; Mariappan, V.
Abstract : Purpose: The study was conducted to assess the level of awareness and acceptance of bank customers towards anti-money laundering practices of banks; and also to understand their constraints in following the bank's AML practice. Design/methodology/approach: The target population was account holders of the banks above the age of 18 years, residing in the States of Puducherry and Tamilnadu. Convenience sampling was adopted in selecting the sample from these states. The sample consisted of 416 customers of the public, private, and foreign banks in India. The responses were collected by administering the pre-tested structured questionnaire. The data was collected during the period June – December 2014. Descriptive and non-parametric tests were applied, and the significance was considered at þ ≤ 0.5. Findings: Respondents showed low level of awareness with regard to terrorism financing (54.6%), usage of banks as a channel for money laundering and terrorism financing activities (74.5%), reporting function of the banks (70.4%), AML and CFT legislation (95.4%), and about the existence of FIU-India and its function (96.9%). The customers were quite aware of money laundering (n=242, 58.2%), and customer identification requirements (n=396, 95.2%). The participants exhibited neutral attitude towards acceptance of AML measures (3.11 ± 1.31). The descriptive analysis showed 97.4% were ready to provide their identification documents to the bank; however, 64.5% of the participants were reluctant to update their KYC particulars when it has not experienced any change; and about 68.3% expressed that banks should not disclose the details of their transactions to any third party including financial intelligence units; Research limitations/implications: The sample constituted only few participants from the foreign sector banks because of the difficulty in identifying the foreign bank customers. Originality/value: An extensive review of literature could not find any research study on the assessment of awareness and acceptance of banking customers towards AML practices in India. Thus this paper attempts to understand the level of awareness and acceptance in the bank customers towards AML practices.